Vascular Neurology Board Review : An Essential Study Guide - Amin, Hardik P.; Schindler, Joseph L. (Springer International Publishing : Imprint: Springer, 2017)
This concise, yet comprehensive review covers the diagnostic and treatment information needed for the vascular neurology board exam. The assembled material is easy-to-read with chapters emphasizing clinically relevant scientific principles that must be mastered by the stroke clinician. Neurology, vascular neurology and neuro-critical care residents and fellows will find this text to be an invaluable preparation guide and a succinct source to complement treatment guidelines and protocols.
Keywords: Medicine.; Cardiology.; Neurology.; elektronické knihy; electronic books